Cost of production of food crops: Kingston & Saint Andrew farm management section - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The purpose of the survey was to generate cost of production of the main crops by parish and to refine the cost of production data collection methodology.